(untitled) (Journal of Hama University, 2022)
The students of the College of Health Sciences are an important component and tributary of the health system, as they play a role in reducing the Corona Virus (Covid-19) pandemic with the increase in cases of infection in Syria, and their correct knowledge about this disease constitutes the essence of that role, so the current descriptive study aims to identify The level of knowledge of 120 students who were selected by the convenient sample method from the Faculty of Health Sciences in Damascus university about the Corona virus (Covid-19), and the data were collected using a tool developed by the researcher, and the study found that more than three quarters of the students have a good level of knowledge about the Corona virus. (Covid-19), and most of them know the ways of prevention, symptoms and groups most affected by the virus. There is no significant relationship between the level of knowledge and demographic variables of students. The study recommended the necessity of continuous evaluation of the information of students of the College of Health Sciences and enhancing their information with the latest reliable information about the virus, and conducting a study on the trends and practices of students of the College of Health Sciences about the virus Covid-19 and the way to prevent and manage infection.